PENERAPAN PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI UPT SPF SD INPRES KAMPUS IKIP - Firqah Muawwidzati; Juhaeda; Baharullah; Aminah (STKIP Subang, 2024)
This research aims to improve the natural science (science) learning outcomes of class VI students at UPT SPF SD Inpres Kampus Ikip through the application of differentiated learning. Differentiated learning is a teaching strategy that is tailored to students' needs, abilities, interests and learning styles, so that each individual can learn optimally. This classroom action research (PTK) was carried out in two cycles, each consisting of planning, implementation, observation and reflection stages. Data is collected through learning results tests, observations, and interviews to measure changes that occur in student learning outcomes. The research results show an increase in student learning outcomes in each cycle. In the first cycle, student learning outcomes showed quite significant improvements, but some students still needed adjustments in the learning methods applied. In the second cycle, learning outcomes increased more sharply along with adjustments made in differentiated learning strategies, such as the use of more diverse media and activities as well as dividing study groups according to students' ability levels. Based on these findings, the application of differentiated learning has proven to be effective in improving science learning outcomes for grade VI students at UPT SPF SD Inpres Kampus Ikip.